Medicine and the Holistic Understanding of the Human Being: Ultrasound Examination as Dialog - Maio, G. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Ultrasound can capture the living nature of a person. This capturing of life depends greatly on experience as well as sense of touch, intuition, sense of speech, and not least a sense for the distinctiveness of every person. Performing ultrasound is not simply the application of a technique but rather a merging of man and technology in the framework of an interpersonal encounter. Therefore, as much should be invested in the interpersonal nature of the encounter as in the development of the technical principles of the ultrasound probe. To effectively perform ultrasound, it is necessary to avoid viewing ultrasound from a purely technical view and to always remember the importance of the relationship to the patient, particularly during the technical examination.
Keywords: ultrasound; physician-patient-relationship; image of man; medical ethics; industrialization of medicine